1981
DOI: 10.1177/030098588101800312
|View full text |Cite
|
Sign up to set email alerts
|

Telangiectatic Osteosarcoma in the Dog

Abstract: Osteosarcoma is a malignant neoplasm of bone that contains at least a sarcomatous stroma and tumor osteoid. It may contain various quantities of neoplastic fibrous connective tissue, cartilage, and bone as well. Histologic classifications of this tumor are based on the proportions of these components. The three most common histologic types are osteoblastic, fibroblastic and chondroblastic [l, 2,4].A rare variant described in both man and dog is the telangiectatic osteosarcoma, also called A recent review of 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 3 publications
1
17
0
Order By: Relevance
“…Furthermore, it is necessary to distinguish osseous HS from telangiectatic osteosarcoma, which is characterized by osteolysis, many blood filled spaces, and osteoid formation [8,16]. These findings are very similar to those of HS in bones, but without osteoid formation [8,16]. In our case, osteoid formation was not found in the sarcoma tissue, and therefore telangiectatic osteosarcoma was also excluded.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Furthermore, it is necessary to distinguish osseous HS from telangiectatic osteosarcoma, which is characterized by osteolysis, many blood filled spaces, and osteoid formation [8,16]. These findings are very similar to those of HS in bones, but without osteoid formation [8,16]. In our case, osteoid formation was not found in the sarcoma tissue, and therefore telangiectatic osteosarcoma was also excluded.…”
supporting
confidence: 53%
“…These findings indicated that the humerus was the primary site, and not secondary metastasis from other organs or tissues with HS. Furthermore, it is necessary to distinguish osseous HS from telangiectatic osteosarcoma, which is characterized by osteolysis, many blood filled spaces, and osteoid formation [8,16]. These findings are very similar to those of HS in bones, but without osteoid formation [8,16].…”
mentioning
confidence: 99%
“…The major diagnostic criteria for TOS are lytic lesions of bone with no bone formation and the presence of many blood‐filled spaces lined by large undifferentiated tumor cells. TOS is characterized by malignant osteoblasts that produce a minimum of osteoid 13 . In the dog in this case, radiographic and histologic examination revealed the characteristic lesions described above.…”
Section: Discussionmentioning
confidence: 59%
“…The 5 designated groups were a) medullary and subperiosteal, b) telangiectatic (TOS), c) sclerosing, d) periosteal, and e) fibrosarcoma (medullary and subperiosteal). Canine osteosarcomas tend to be classified into histologic subtypes based on the quality and quantity of extracellular matrix (osteoblastic, chondroblastic, 9,10 and fibroblastic 11 ), the degree of differentiation (poorly differentiated or undifferentiated), the relative abundance of giant cells (giant‐cell, giant‐cell‐rich, and osteoclast‐rich 12 subtypes), and the dominance of blood‐filled cystic lesions (telangiectatic 13–15 ). A sclerotic subtype also has been described in dogs 16,17 .…”
mentioning
confidence: 99%
“…The histologic features of OS, however, vary greatly from tumor to tumor and within tumors themselves. Multiple types of well-and undifferentiated cells and matrix are often observed in a single tumor, 16,25,26 which may be why subclassification of OS has not yielded significant differences in the prognosis of human and canine OS. 18,40 In human OS, histologic grading of the tumor, in contrast to subclassification, serves as a good indicator for prognosis.…”
mentioning
confidence: 99%